2022
DOI: 10.3389/fnut.2022.846808
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Quinoa Flour on Wheat Dough Quality, Baking Quality, and in vitro Starch Digestibility of the Crispy Biscuits

Abstract: Quinoa is a pseudo-cereal which has excellent nutritional and functional properties due to its high content of nutrients, such as polyphenols and flavonoids, and therefore quinoa serves as an excellent supplement to make healthy and functional foods. The present study was aimed to evaluate the quality characteristics of wheat doughs and crispy biscuits supplemented with different amount of quinoa flour. The results showed that when more wheat flour was substituted by quinoa flour, proportion of unextractable p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…This is outlined in the absence of gluten and protein network structure in PF dough, resulting in higher protein weakening degrees and decreased dough consistency. Similar results were reported by Yanrong Ma et al [30] when different amounts of quinoa flour were supplemented with refined wheat flour in making crispy biscuits.…”
Section: Analysis Of Mixing and Pasting Propertiessupporting
confidence: 88%
“…This is outlined in the absence of gluten and protein network structure in PF dough, resulting in higher protein weakening degrees and decreased dough consistency. Similar results were reported by Yanrong Ma et al [30] when different amounts of quinoa flour were supplemented with refined wheat flour in making crispy biscuits.…”
Section: Analysis Of Mixing and Pasting Propertiessupporting
confidence: 88%
“…Our new 1BS-18H wheat is not transgenic because there is no insertion of foreign genes. Our preliminary study showed that 1BS-18H wheat retained the unique viscoelastic properties of wheat for use in products such as bread and noodles by tensile test for gluten dough, and its moisture, protein, and ash content were similar to those of common wheat as reported by Ma et al [ 17 ]. We previously reported that ω5-gliadin was detected in 1BS-18H gluten only approximately 23% of that in Hokushin gluten [ 18 ], and the intravenous challenge of 1BS-18H gluten did not elicit an allergic reaction in rats sensitized to ω5-gliadin [ 19 ].…”
Section: Introductionsupporting
confidence: 79%
“…The presence of quinoa flour in bread formulations in this study can probably reduce starch digestibility and increase the resistant starch content. It was reported the starch digestibility of the crispy biscuits decreased with the increase of quinoa flour [32].…”
Section: Resultsmentioning
confidence: 97%